2022
DOI: 10.1371/journal.pone.0263414
|View full text |Cite
|
Sign up to set email alerts
|

Creating a social movement to engage communities in physical activity: A mixed methods study of motivations to engagement

Abstract: Throughout the world social isolation and loneliness are common and both have several adverse impacts on health and wellbeing. We are designed to live in close-knit communities and we thrive in close co-operation, however, modern life isolates us from others. To reduce the burden of loneliness and social isolation we need to find strategies to reconnect people to each other, their place and provide a common purpose. Social movements aim to create healthier communities by connecting people to each other and giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Regarding organizational and environmental aspects, during the focus groups, the expert emphasized the role of the family, friends, and group relationships in supporting the engagement in judo of older practitioners, as well as in decreasing the social isolation, loneliness, and depression, which increase with advancing age [ 105 , 115 ]. To deepen social relations while training and increase engagement in daily physical activity, the experts suggested that a judo program for older adults should be focused on the enjoyment of the relationships and cooperation with other judo practitioners and the personal improvements rather than on the communication of the benefits of physical activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding organizational and environmental aspects, during the focus groups, the expert emphasized the role of the family, friends, and group relationships in supporting the engagement in judo of older practitioners, as well as in decreasing the social isolation, loneliness, and depression, which increase with advancing age [ 105 , 115 ]. To deepen social relations while training and increase engagement in daily physical activity, the experts suggested that a judo program for older adults should be focused on the enjoyment of the relationships and cooperation with other judo practitioners and the personal improvements rather than on the communication of the benefits of physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…To deepen social relations while training and increase engagement in daily physical activity, the experts suggested that a judo program for older adults should be focused on the enjoyment of the relationships and cooperation with other judo practitioners and the personal improvements rather than on the communication of the benefits of physical activity. In this respect, the intrinsic values of judo could be used as a means to unify age-related communities and to foster family relationships breaking barriers between different generations when embracing an intergenerational approach with children and grandchildren [ 115 ]. Finally, to foster positive feelings, social interaction, and an open atmosphere, experts highlighted the role of background music (music genres suggested included oldies, pop, nursery rhymes, and world-famous songs) while training judo.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we must start considering that “physical” health discourse should not establish what is primary and secondary in adolescents’ lives. Recent evidence has demonstrated that people may value social messages about behavior change more than discourse on disease prevention (Harris et al, 2022; Williamson et al, 2020). Therefore, tobacco and alcohol use, bullying, sexual health (in broader terms), and mental health must also be a school's primary health goals (Shackleton et al, 2016).…”
Section: Discussionmentioning
confidence: 99%